Redox balance in elite female athletes: differences based on sport types - Arsic, A.; Vucic, V.; Glibeic, M.; Popovic, T.; Debeljak-Martacic, J.; Cubrilo, D.; Ahmetovic, Z.; Peric, D.; Borozan, S.; Djuric, D.; Jakovlevic, V. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of the present study was to analyze changes in redox balance throughout parameters of oxidative stress and activities of antioxidant enzymes in elite female water polo (N.=15) and football players (N.=19) aged between 20 and 23. Fourteen age-matched sedentary women were also included in the study. METHODS: Blood sampling was performed to measure levels of lipid peroxidation (MDA), total antioxidant status (TAS), superoxide anion radical (O2¯), hydrogen peroxide (H2O2), reduced glutathione (GSH), oxidized glutathione (GSSG), nitrites, superoxide dismutase activity (SOD), catalase activity (CAT) and glutathione-peroxidase activity (GPx). RESULTS: Levels of MDA, TAS, GSSG and H2O2 were significantly higher in athletes than in the control women. Football players had higher levels of O2¯ than the other two groups. Activity of SOD was higher in water polo players when compared with the football and control groups, CAT was increased in all athletes, while GPx did not differ among groups. CONCLUSIONS: Therefore, prolonged intensive training markedly increases oxidative stress in women, which depends on the type of sport. Lower concentration of O2¯ and increased activity of SOD in water polo players compared to football players suggest that mechanisms of adaptation of antioxidative defense are related to the type of exercise.